2021
DOI: 10.1186/s12957-021-02339-7
|View full text |Cite
|
Sign up to set email alerts
|

Cyanidin-3-glucoside suppresses the progression of lung adenocarcinoma by downregulating TP53I3 and inhibiting PI3K/AKT/mTOR pathway

Abstract: Background The aim of this study is to unravel the role of Cyanidin-3-glucoside (C3G) and its potential mechanisms in lung adenocarcinoma (LUAD). Methods The cell clones, proliferation, apoptosis, migration, and invasion in H1299 and A549 cells were determined by colony formation assay, 5-ethynyl-20 deoxyuridine (EdU) assay, flow cytometry, and transwell assay, respectively. The expression of p53-induced gene 3 (TP53I3) was assessed and the prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Lu et al [ 158 ], for instance, showed that the ACNs extracted from the fruits of Vitis coignetiae Pulliat, widely used in Korean folk medicine to treat inflammatory diseases and cancers, inhibit the expression of several transcription and growth factors that promote proliferation, angiogenesis, invasion, and migration of non-small cell LC (NSCLC) cells. Similar results were obtained when LC model cells were assayed with Cy3glu and Dp solutions, unveiling the downregulation of specific pathways [ 159 ] and transcription factors [ 160 ].…”
Section: Significance Of Acns From Plants To Human Health Benefitssupporting
confidence: 68%
“…Lu et al [ 158 ], for instance, showed that the ACNs extracted from the fruits of Vitis coignetiae Pulliat, widely used in Korean folk medicine to treat inflammatory diseases and cancers, inhibit the expression of several transcription and growth factors that promote proliferation, angiogenesis, invasion, and migration of non-small cell LC (NSCLC) cells. Similar results were obtained when LC model cells were assayed with Cy3glu and Dp solutions, unveiling the downregulation of specific pathways [ 159 ] and transcription factors [ 160 ].…”
Section: Significance Of Acns From Plants To Human Health Benefitssupporting
confidence: 68%
“…Besides these C3G also facilitates apoptosis by inhibiting the activation of the mammalian target of rapamycin (mTOR) as well as the protein kinase B (AKT) pathway and suppression of TP53I3 in LC cells. This data suggest that C3G is an effective compound for treating LC (Chen et al, 2021).…”
Section: Types Of Cancersmentioning
confidence: 89%
“…Previous studies had shown that activation of mTOR promotes tumor growth and metastasis [ 17 ]. The PIK3CA mutation is also a common feature of LUAD, which is related to a poor prognosis [ 18 ]. Alterations in the cell cycle and PI3K pathways were associated with recurrence of LUAD [ 19 ].…”
Section: Discussionmentioning
confidence: 99%